Urinary Biomarkers of Acute Kidney Injury in Patients with Liver Cirrhosis. (6th April 2014) - Qasem, Anass Ahmed; Farag, Salama Elsayed; Hamed, Emad; Emara, Mohamed; Bihery, Ahmed; Pasha, Heba
Abstract : Acute kidney injury (AKI) is a common complication in cirrhotic patients. Serum creatinine is a poor biomarker for detection of renal impairment in cirrhotic patients. This study aimed to evaluate urinary neutrophil gelatinase-associated lipocalin (NGAL) and urinary interleukin-18 (IL-18) as early biomarkers of acute kidney injury in cirrhotic patients. 160 patients with cirrhosis admitted to the Liver Units at Zagazig University Hospitals were classified into three groups: (I) nonascitic patients, (II) ascitic patients without renal impairment, and (III) ascitic patients with renal impairment. Patients with renal impairment were further divided into four subgroups: [A] prerenal azotemia, [B] chronic kidney disease (CKD), [C] hepatorenal syndrome (HRS), and [D] acute tubular necrosis (ATN). Significant elevation of both urinary NGAL and urinary IL-18 in cirrhotic patients with renal impairment especially in patients with ATN was observed. Urinary NGAL and urinary IL-18 have the ability to differentiate between AKI types in patients with cirrhosis. This could improve risk stratification for patients admitted to the hospital with cirrhosis, perhaps leading to early ICU admission, transplant evaluation, and prompt initiation of HRS therapy and early management of AKI.